1993
DOI: 10.1093/nar/21.11.2591
|View full text |Cite
|
Sign up to set email alerts
|

The adenovirus DNA binding protein enhances intermolecular DNA renaturation but inhibits intramolecular DNA renaturation

Abstract: The Adenovirus DNA binding protein (DBP) imposes a regular, rigid and extended conformation on single stranded DNA (ssDNA) and removes secondary structure. Here we show that DBP promotes renaturation of complementary single DNA strands. Enhancement of intermolecular renaturation is sequence independent, can be observed over a broad range of ionic conditions and occurs only when the DNA strands are completely covered with DBP. When one strand of DNA is covered with DBP and its complementary strand with T4 gene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 49 publications
(56 reference statements)
1
26
0
Order By: Relevance
“…This would suggest that the addition of NC to an oligomer capable of forming a stable hairpin should actually promote hairpin formation. One possibility is that NC could unfold single-stranded DNA and hold it in a linear form, in a manner similar to the adenovirus DNA binding protein (40). This would also be consistent with reports that NC can unfold secondary structures in RNA and DNA, leading to increased RT polymerization rates through regions containing secondary structure (19,38).…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This would suggest that the addition of NC to an oligomer capable of forming a stable hairpin should actually promote hairpin formation. One possibility is that NC could unfold single-stranded DNA and hold it in a linear form, in a manner similar to the adenovirus DNA binding protein (40). This would also be consistent with reports that NC can unfold secondary structures in RNA and DNA, leading to increased RT polymerization rates through regions containing secondary structure (19,38).…”
Section: Resultssupporting
confidence: 83%
“…Therefore, the annealing of a strand transfer acceptor cannot be the only mechanism that prevents self-priming. One possibility is that NC interferes with the formation of hairpins by preventing bending of the hairpin DNA (24,40). However, we present evidence that this is not the mechanism that prevents self-priming.…”
mentioning
confidence: 54%
“…However, no helicase is needed in the elongation phase of adenovirus replication. Recently we have shown that DBP by itself stimulates DNA unwinding when the duplex has a singlestranded extension [31], which suggests that DBP is the unwinding protein during chain elongation. Thus unwinding occurs independent of ATP and is optimal at low M$ concentrations, similar to the conditions required for in vitro adenovirus DNA replication [31].…”
Section: Discussionmentioning
confidence: 98%
“…Employing templates in which the origin is partially or completely single stranded no stimulation *Corresponding author. Fax: (31) (30) 888443. by ATP was observed suggesting that ATP might be required for origin opening [5,9,10]. Furthermore, none of the proteins involved in replication has ATPase activity, moreover, non-hydrolysable ATP analogues such as ATPyS, AMP-PNP and AMP-PCP also stimulate the reaction [lo].…”
Section: Introductionmentioning
confidence: 99%
“…Such intramolecular interactions are thought to occur during Ad replication when the ITRs in single-stranded intermediates form a so-called pan-handle structure (7,19). However, in vitro stud-ies have shown that the Ad DNA-binding protein, when present in sufficient amounts, inhibits intramolecular renaturation and enhances intermolecular renaturation (22). The inhibitory effect was attributed to the rigid structure of single-stranded DNA bound to DNA-binding protein and which might, therefore, be weaker on longer templates.…”
Section: Discussionmentioning
confidence: 99%